2010
DOI: 10.1021/jf9030162
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phenol, o-Cresol, and p-Cresol with a Clay-Rich Soil Sample

Abstract: The present paper describes an interaction study of phenol, o-cresol, and p-cresol with a rich-clay soil sample (clay content of 62.3%). Experiments performed using long contact times, in concentrations of 50.0 mg L(-1) showed practically no signal of phenol, o-cresol, and p-cresol after 48, 72, and 120 h, respectively, suggesting a sorption process. Sorption experiments in the period of 24 h were carried out with the phenolic compounds in concentrations between 5.00 and 500.0 mg L(-1), and negligible interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Phenol and phenolic compounds are considered environmental contaminants for soil and bodies of water. However, a previous study evaluated the interaction of phenolic compounds with soil sample collected near a shale industry and concluded that the phenolic species in these soil samples would be biodegraded or even continue to be present as nonextractable residues, and for this reason, no risks of groundwater contamination could take place (Dolatto et al, 2010). Since polycyclic aromatic hydrocarbons (PAHs) are potentially toxic to the environment, resulting in absorption and accumulation in the food chain (Nicolini et al, 2011), we also analyzed the presence of PAHs (Benz[a]pyrene, Benz[b]fluoranthene, Benz[k]Fluorene, Chrysene, Acenaphthylene, Fluorine, Anthracene, Benz[g,h,i]perylene, Phenanthrene, Dibenz[a,h]anthracene, Indeno[1,2,3-cd]pyrene, Pyrene, Anthracene, Fluoranthene, Naphthalene, and Benz[a]anthracene) in the SW samples.…”
Section: Physical-chemical Characterization Of Shale Watermentioning
confidence: 99%
“…Phenol and phenolic compounds are considered environmental contaminants for soil and bodies of water. However, a previous study evaluated the interaction of phenolic compounds with soil sample collected near a shale industry and concluded that the phenolic species in these soil samples would be biodegraded or even continue to be present as nonextractable residues, and for this reason, no risks of groundwater contamination could take place (Dolatto et al, 2010). Since polycyclic aromatic hydrocarbons (PAHs) are potentially toxic to the environment, resulting in absorption and accumulation in the food chain (Nicolini et al, 2011), we also analyzed the presence of PAHs (Benz[a]pyrene, Benz[b]fluoranthene, Benz[k]Fluorene, Chrysene, Acenaphthylene, Fluorine, Anthracene, Benz[g,h,i]perylene, Phenanthrene, Dibenz[a,h]anthracene, Indeno[1,2,3-cd]pyrene, Pyrene, Anthracene, Fluoranthene, Naphthalene, and Benz[a]anthracene) in the SW samples.…”
Section: Physical-chemical Characterization Of Shale Watermentioning
confidence: 99%
“…Among the principal sources of phenol wastes in the environment are oil refineries, the pharmaceutical and the polymer industries. The appearance of phenol and its derivatives in the environment may be associated with the use of these compounds as intermediates in the synthesis of plastics, dyes and pesticides . Biological processes generally do not remove refractory compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of phenol and its derivatives in the environment may be associated with the use of these compounds as intermediates in the synthesis of plastics, dyes and pesticides. 4,5 Biological processes generally do not remove refractory compounds. In most cases, high concentrations of these can inhibit the performance of or be toxic to the microorganisms that are responsible for the removal of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…5, 2012 charge of the soil particles and the phenolic compounds. 8 Hence, the above mentioned leaching process is highly favorable.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high volumes of toxic solvents are employed and low sampling rate are attained (mainly due to the sample preparation) in order to obtain the clean up and enrichment steps. Other possibility is the compound determination by UV molecular absorption spectrophotometry, 6,8 but with higher limit of quantification, as well as several spectral interferences. The official spectrophotometric method of 4-aminoantipyrine (4-AAP) presents better selectivity and LOQ for total phenolic determination in aqueous samples.…”
Section: Introductionmentioning
confidence: 99%